2020
DOI: 10.1021/acs.jpcc.0c04437
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Solvent Effects on the Hydrodeoxygenation of Propionic Acid over a Ni(111) Catalyst Model

Abstract: The effect of two solvents, liquid water and 1,4-dioxane, has been studied from first-principles on the hydrodeoxygenation of propionic acid over a Ni(111) catalyst surface model. A mean-field microkinetic model was developed to investigate these effects at a temperature of 473 K. Under all reaction conditions, a decarbonylation mechanism is favored significantly over a decarboxylation pathway. Although no significant solvent effects were observed on the decarbonylation rate, a substantial solvent stabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 57 publications
2
27
1
Order By: Relevance
“…21−25 Examples of implicit models are the conductor-like screening model (COSMO 26 ) which uses an approximation of the solvent as a dielectric continuum with a cavity for the molecule. 27,28 Explicit models may make use of molecular dynamics and density functional theory (DFT). 29,30 Explicit hybrid quantum-mechanical/molecular mechanics (QM/MM) have been used to capture the effect for phenol on Pt(111) in water.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21−25 Examples of implicit models are the conductor-like screening model (COSMO 26 ) which uses an approximation of the solvent as a dielectric continuum with a cavity for the molecule. 27,28 Explicit models may make use of molecular dynamics and density functional theory (DFT). 29,30 Explicit hybrid quantum-mechanical/molecular mechanics (QM/MM) have been used to capture the effect for phenol on Pt(111) in water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Particularly important would be to develop methods for estimating the effect of liquid solvents on the energies of adsorbed reaction intermediates and transition states in catalytic and electrocatalytic reaction mechanisms, as this would facilitate the development of microkinetic models for estimating reaction kinetics that have been so fruitful in gas-phase catalysis research, but sorely lacking for reactions in liquid solutions. There have been numerous studies to compare heats of adsorption measured in liquid solvents with those in the gas phase and to use simulations to clarify the role of the solvent. ,,,, There are several reviews and viewpoints that discuss the challenges involved in modeling solvent effects. , Generally, modeling efforts to speed up computational work incorporating solvent effects include implicit modeling of the solvent as a homogeneous constant dielectric continuum, bilayer adsorption (ice model), explicit modeling of the solvent by inclusion of solvent molecules in the simulation, and mixtures of implicit and explicit solvation. Examples of implicit models are the conductor-like screening model (COSMO) which uses an approximation of the solvent as a dielectric continuum with a cavity for the molecule. , Explicit models may make use of molecular dynamics and density functional theory (DFT). , Explicit hybrid quantum-mechanical/molecular mechanics (QM/MM) have been used to capture the effect for phenol on Pt(111) in water …”
Section: Introductionmentioning
confidence: 99%
“…The role of solvents in catalytic transformations occurring at a solid-liquid interface is typically ascribed to: heightened importance of mass transfer effects, nature of solvent (polarity etc.) [35][36][37] , competitive adsorption between solvent molecules and adsorbed moieties 32,38,39 , direct participation of the solvent in the reaction coordinate 40 , and/or relative stabilization of reactant, transition and/or product state of elementary reactions [41][42][43] . These effects in turn can lead to a change in reaction mechanism, reaction kinetics, selectivity, and overall catalyst lifetime.…”
mentioning
confidence: 99%
“…Figure illustrates the reaction network investigated for the HDO of propanoic acid over a Cu(111) surface. The reaction network contains all elementary reaction steps that were previously considered in our prior studies for the decarbonylation and decarboxylation of propanoic acid to produce alkenes and alkanes on various transition-metal surfaces. In addition, reaction pathways for propanol and propionaldehyde production are considered in the reaction network based on our prior study of the HDO of PAc on the Pt(111) surface . The conversion of PAc (a dioxy species) to propanol or propionaldehyde (a monoxy species) must, at minimum, involve one C–O bond scission step followed by hydrogenation steps, although it is not obvious when that C–O bond scission occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have computationally explored the HDO of PAc to C 2 alkanes on Pd, Ru, and Ni metal surfaces by a combination of density functional theory (DFT) calculations and microkinetic modeling. In these studies, we found that the DCN pathway is preferred over the DCX pathway. In another study, we observed alcohol and aldehyde formation in addition to decarbonylation products during the vapor-phase HDO of PAc over a Pt surface . In condensed-phase reaction environments, the reaction products shift away from alkanes toward alcohols and aldehydes.…”
Section: Introductionmentioning
confidence: 96%